Global trends and disease burden of elderly male breast cancer, 1990-2021: a population-based study - Liu, Shaochun; Xu, Jian; Zhang, Han; Tang, Yuhan; Han, Xiaoxi; Xiong, Wenjing; Fan, Linlin; Su, Chang; Sui, Zhiqi; Zhao, Wenhui (Frontiers in Endocrinology, 2026)
ObjectiveTo assess global, regional, and national trends in the burden of elderly male breast cancer (EMBC) from 1990 to 2021 and to evaluate projected patterns to 2040.MethodsEstimates were obtained from the Global Burden of Disease 2021 study. Age-standardised incidence, mortality, and disability-adjusted life year rates (ASIR, ASMR, ASDR) were analysed across all countries and Sociodemographic Index (SDI) strata. Long-term changes were quantified using the average annual percent change derived from log-linear models. Joinpoint regression identified temporal inflection points. Age–period–cohort (APC) models characterise independent temporal effects. Mortality changes were decomposed into components attributable to population growth, ageing, and epidemiological change. Inequality was assessed using slope and concentration indexes. Attributable mortality and DALYs were evaluated for alcohol use, dietary risks, and tobacco. Future rates to 2040 were estimated using a Bayesian age–period–cohort (BAPC) model.ResultsGlobally, EMBC incidence, mortality, and DALYs increased from 1990 to 2021, with average annual percent changes(AAPC) of 1.8 (95% CI, confidence interval, 1.63 to 1.98), 0.58 (95% CI 0.38 to 0.77), and 0.68 (95% CI 0.43 to 0.92). East Asia recorded the steepest rise in incidence, increasing from 1.65 (95% UI, uncertainty interval, 1.16 to 2.42) to 6.65 per 100000 population (95% UI 2.77 to 9.78). The middle SDI quintile showed the largest increases in all three metrics, rising from 1.62 (95% UI 1.18 to 2.09) to 4.92 per 100000 population (95% UI 2.26 to 6.81). APC analysis indicated pronounced period and cohort effects in middle and low-middle SDI settings. Decomposition identified population growth as the dominant driver of rising burden. Alcohol use and dietary risks accounted for most increases in mortality and DALYs, while tobacco contributed minimally. Cross-country inequality was modest for incidence but more marked for mortality and DALYs. Projections suggest that age-standardised rates will decline gradually by 2040, although absolute case numbers may continue to rise in rapidly ageing regions.ConclusionThe global burden of EMBC continues to increase, with substantial regional and socioeconomic disparities. Although age-standardised rates are projected to decline, population ageing is expected to sustain or expand absolute numbers of cases and deaths.